Evaluación de la calidad de guías de práctica clínica en personas que han sufrido amputación de miembro inferior : revisión de la literatura y evaluación con el instrumento AGREE II (2016)
ABSTRACT: Quality appraisal of clinical practice guidelines about lower-limb amputees: literature review and appraisal with AGREE II instrument The Colombian Ministry of Health and Social Protection called on scientific organizations for the creation of a Clinical Practice Guideline (CPG) in order to provide recommendations for the preoperative, perioperative, and postoperative care of people with amputation of a lower limb due to medical or traumatic causes. This paper shows the quality appraisal by means of the AGREE II instrument of GPC published to date about this condition as one of the initial steps in the construction of the needed guide. After a systematic search in different specialized databases and applying criteria of inclusion and exclusion 7 CPG were evaluated. The best-qualified domain was the 1 in which all CPG had a percentage of compliance higher than 60 %, and the worst one was the 5 with only two CPG that exceeded 60 % of compliance. The best qualified CPG was the one created by the Dutch Society of Physical Medicine and Rehabilitation. To date, this is the first paper that evaluates the quality of CPGs that deal with people with lower limb amputation.